PENINGKATAN KINERJA YANG DIPENGARUHI OLEH FAKTOR DISIPLIN KERJA DAN PENGARAHAN (Studi Pada Kineja Personel Polres Sampang) - Achmat Rochan; Nugroho Mardi Wibowo; Subijanto; Chamariyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 237 personnel. The objectives of this study are 1). To test and analyze whether work discipline and direction simultaneously influence the performance of the Sampang Police personnel. 2). To test and analyze whether work discipline has a significant effect on the performance of the Sampang Police personnel. 3.) To test and analyze whether the briefing has a significant effect on the performance of the Sampang Police personnel. 1.) Work discipline, direction and promotion simultaneously had a significant effect on the performance of the Sampang Police personnel. 2.) Work discipline has a significant influence and has an influence on improving the performance of the Sampang Police personnel. 3.) Briefing has a significant effect on improving the performance of the Sampang Police personnel.